Amyloidosis and its related factors in Turkish patients with familial Mediterranean fever: a multicentre study - DİRESKENELİ, RAFİ HANER (OXFORD UNIV PRESS, 2014)
Methods. Fifteen centres from the different geographical regions of Turkey were included in the study. Detailed demographic and medical data based on a structured questionnaire and medical records were collected. The diagnosis of amyloidosis was based on histological proof of congophilic fibrillar deposits in tissue biopsy specimens. Results. There were 2246 FMF patients. The male/female ratio was 0.87 (1049/1197). The mean age of the patients was 34.5 years (s.d. 11.9). Peritonitis was the most frequent clinical finding and it was present in 94.6% of patients. Genetic testing was available in 1719 patients (76.5%). The most frequently observed genotype was homozygous M694V mutation, which was present in 413 (24%) patients. Amyloidosis was present in 193 patients (8.6%). Male sex, arthritis, delay in diagnosis, M694V genotype, patients with end-stage renal disease (ESRD) and family history of amyloidosis and ESRD were significantly more prevalent in patients with amyloidosis compared with the amyloidosis-negative subjects. Patients with homozygous M694V mutations had a 6-fold higher risk of amyloidosis compared with the other genotypes (95% CI 4.29, 8.7, P < 0.001). Conclusion. In this nationwide study we found that 8.6% of our FMF patients had amyloidosis and homozygosity for M694V was the most common mutation in these patients. The latter finding confirms the association of homozygous M694V mutation with amyloidosis in Turkish FMF patients.
Keywords: familial Mediterranean fever; amyloidosis; prevalence; RISK-FACTOR; MEFV; M694V; GENE; PROGNOSIS; GENOTYPE; FMF